2012
DOI: 10.4137/aci.s8864
|View full text |Cite
|
Sign up to set email alerts
|

Two chromatographic Methods for the Determination of some Antimigraine Drugs

Abstract: Two stability indicating chromatographic methods were proposed for the determination of almotriptan, eletriptan, and rizatriptan, in presence of their acid degradation products. The first method is a quantitative densitometric thin layer chromatography. The developing systems were; acetonitrile: methanol: dichloromethane: ammonia (10:6:3:1 v/v), ethyl acetate: methanol: ammonia (15:4:1 v/v), and methanol: acetonitrile: ammonia (9:4:1 v/v) for almotriptan, eletriptan and rizatriptan respectively. The TLC plates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…ciklohexán-diklórmetán-dietilamin valamint kloroform-metanol-etilacetát-ammónia. Egy másik közlemény butanol-ecetsav-víz mozgófázisokról számol be, különböző szerves módosítókkal [29][30].…”
Section: Generációkunclassified
“…ciklohexán-diklórmetán-dietilamin valamint kloroform-metanol-etilacetát-ammónia. Egy másik közlemény butanol-ecetsav-víz mozgófázisokról számol be, különböző szerves módosítókkal [29][30].…”
Section: Generációkunclassified
“…HPLC [7-9] and HPTLC [10] methods have also been used for quantitative determination of rizatriptan in bulk drug or pharmaceutical dosage forms. Furtheremore, few spectrophotometric methods were reported in the literature for the determination of rizatriptan in dosage forms [11-16].…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey revealed that very few analytical methods have been reported for the determination of eletriptan in pure drug, pharmaceutical dosage forms, and biological samples using HPLC [4][5][6] and LC-MS [7] techniques. A few methods are found in the literature for the determination of ELT in pharmaceuticals and include spectrophotometry [8][9][10][11][12] and spectrofluorimetry [11,12].…”
Section: Introductionmentioning
confidence: 99%